Thinking about the problems of democracy from Hannah Arendt - Fontes, Paulo Vitorino (2022)
In recent decades we have witnessed the emptying of the ideal of participatory democracy. If, on the one hand, we go back to the original formulations of the 1960s and 1970s, we see that these indicated the need to expand the spaces of collective democratic management in daily life, particularly in the workplace. But, on the other hand, the models of the following decades accepted the circumscription of democratic practices to the state. In a parallel movement, the critique of representative institutions and the political passivity they promote was set aside in favour of a perception in which the difference between participation and representation is practically annulled. With this, the radicality of the critique of the participation deficit in liberal democracies is lost. In the context of post-modernity, in which the ailments of modernity have not been healed, together with the generalised lack of interest in public affairs, especially among the younger generations, there is an urgent need to revitalise sleeping democracies, mostly in the Western world. Our work is built on Hannah Arendt's thought, committed to rehabilitating the space of politics, and on the dialogue with other authors, but also on the investigation of psychoanalytic contributions, following the tradition of German critical theory, in the search for antidotes to the dangers that Western democracies face, more specifically the right-wing populist escalation and the disintegrating threat of an instrumental rationality that is colonising all domains of our existence. It becomes pertinent, as an objective for our work, to revisit Arendt's great questions and, based on existing scientific knowledge, to imagine and conceptualise new forms of inclusion and social and political participation that may renew the democratic system. Here, we can only enunciate this project, which will be developed in a broader research context. [da Introdução]